2023
DOI: 10.3389/fenvs.2022.1076103
|View full text |Cite
|
Sign up to set email alerts
|

Can the green credit policy stimulate green innovation of heavily polluting enterprises in China?

Abstract: Introduction: The requirement for more funds has been a significant challenge for China’s heavily polluting enterprises (HPEs) to embark on green innovation.Methods: This study takes China’s 2012 Green Credit Guidelines (GCGs) as a quasi-natural experiment to examine their effect on the quality and quantity of green innovation in HPEs. Using the data of Chinese listed companies from 2007 to 2020 and the difference-in-differences (DID) model.Results: We found that the Green Credit Guidelines could significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Although the above empirical results show that mixed ownership reform contributes to the improvement of enterprises' carbon performance, it cannot be ruled out that some other factors may interfere with the relationship between mixed ownership reform and carbon performance [42]. In 2011, the National Development and Reform Commission of China issued a Notice on Launching Pilot Carbon Emission Trading Programs, requiring Beijing, Shanghai, Chongqing, Tianjin, Guangdong, Shenzhen, Hubei, and other provinces and municipalities to launch pilot carbon emission trading programs.…”
Section: Eliminate Other Distractionsmentioning
confidence: 87%
“…Although the above empirical results show that mixed ownership reform contributes to the improvement of enterprises' carbon performance, it cannot be ruled out that some other factors may interfere with the relationship between mixed ownership reform and carbon performance [42]. In 2011, the National Development and Reform Commission of China issued a Notice on Launching Pilot Carbon Emission Trading Programs, requiring Beijing, Shanghai, Chongqing, Tianjin, Guangdong, Shenzhen, Hubei, and other provinces and municipalities to launch pilot carbon emission trading programs.…”
Section: Eliminate Other Distractionsmentioning
confidence: 87%
“…Otherwise, it takes on a value of 0. The compilation of heavy-polluting firms is founded on the revised Guidelines on Industry Classification of Listed Firms by the China Securities Regulatory Commission in 2012, along with the List of Listed Firms for Environmental Verification Industry Classification in 2008 [35,58,59]. This encompasses sectors such as thermal power, steel, cement, electrolytic aluminum, coal, metallurgy, building materials, mining, chemicals, petrochemicals, pharmaceuticals, light, textiles, and leather (codes: B06, B07, B08, B09, B11, C17, C18, C19, C22, C25, C26, C27, C28, C29, C30, C31, C32, C33, D44.).…”
Section: Explanatory Variablementioning
confidence: 99%
“…Based on the background of heterogeneous industries, Shen [23] identified the optimal degree of industrial regulation in China through non-linear analysis of environmental regulation and efficiency.Li Ling and Tao Feng [24] found that in China's medium and low pollution industries, the impact of environmental regulation on green TFP and the impact of technological innovation on technological efficiency exhibit a U-shaped curve, and their speed of breaking through the U-shaped inflection point is faster than that of productivity and technological innovation. Bing et al [25] pointed out that different levels of environmental regulations have different effects on corporate green innovation.Tang et al [26] believe that compared to the other two types of environmental regulations, ER1, as the initial stage of green industry development, plays a much greater role in promoting innovation in the green industry. ER2 and ER3 experience stable growth during the high-income period of the economy,while ER1 serves as the foundation.…”
Section: Research On the Relationship Between Environmental Regulatio...mentioning
confidence: 99%